Empowering software startups with agile methods and practices: a design science research - Javdani Gandomani, Taghi; Zulzalil, Hazura; Bahsoon, Rami (John Wiley and Sons, 2024)
The growing number of software startups has witnessed an open debate on the suitability and appropriateness of commonly used software development methodologies, including agile software development methodologies and practices. Startups, for example, tend to focus on producing minimum viable product, which challenge the use of these methods and calls for bespoke adaptation of these practices to suit startups. Agile adoption is not easy for software startup teams due to unreadiness, inadequate preparation and weak structure of these teams, focusing only on small part of agile practices, and high uncertainty in essential requirements and proper technology. A review of the state-of-the-art reports on limited number of studies that have investigated the adoption of agile methods and practices to best suit the requirements software startups. This study uses design science research methodology to address this gap and develop a guideline for agile adaptation specifically for software startups. The developed guideline was validated and improved with the participation of 23 experts from 7 software startup teams through survey questionnaires and open discussion. This guideline includes 13 recommendations, categorized into three sections: selection of agile methods and practices, preparation for adaptation, and the adaptation of agile methods and practices. Evaluation of the results shows the simplicity of understanding the guideline, its usefulness, and its support for the expected agility of the software development process.